Kualitas Pelayanan Publik Pada Dinas Kependudukan Dan Catatan Sipil Kabupaten Dompu - Novita, Anggun Putri; Wardani, Rosyia; Helmida, Baiq Ertin (CV. ITTC INDONESIA, 2022)
This study aims to determine the quality of public services at the Department of Population and Civil Registry of Dompu Regency. The variable in this study is the single variable of Public Service Quality. The population of this study were residents of Dompu Regency aged 17 years and over who received services at the Department of Population and Civil Registry of Dompu Regency. The sample was determined by the Incidental Sampling technique with a total of 100 respondents who provided services at the Population and Civil Registry Office of Dompu Regency. Data were analyzed using SPSS. The results of this study indicate that the quality of public services at the Department of Population and Civil Registry of Dompu Regency is 70% higher than the average ideal value (accepted), in other words Ho, namely the quality of public services at the Department of Population and Civil Registry of Dompu Regency is lower 70 % (rejected). The conclusion of this research is that the quality of public services at the Department of Population and Civil Registration of Dompu Regency has met most of the expectations of the Dompu people.